ADULT INTUSSUSCEPTION - A SURGICAL DILEMMA - Rathore, M A; Andrabi, S I H; Mansha, M (Journal of Ayub Medical College Abbottabad, 2006)
Background: Adult intussusception is rare. It is expected to be found in 1/30,000 of all hospital admissions, 1/1300 of all abdominal operations, 1/30-1/100 of all cases operated for intestinal obstruction and one case of adult intussusception for every 20 childhood ones. Methods: The authors encountered 4 cases of adult intussusception. M:F ratio was 1:1. Mean age was 47years. Small bowel obstruction was documented in all. They were investigated by radiographs, ultrasound exam, barium studies, endoscopy and CT scan. Results: All however were diagnosed at operation although some pre-operative suspicion was raised in one case. All had a laparotomy. Two were ileo-ileal and two ileo-caecal intussusceptions. One was chronic intussusceptions and three sub-acute. One intussusception had a malignancy (lymphoma) as a lead point. Two had a submucous lipoma at the apex. In an interesting case the suture knot from a recent small bowel anastomosis (2-3 weeks prior) was forming the lead point of the intussusception! The 2 ileo-ileal intussusceptions had segmental resection. Right hemicolectomy was done for the 2 ileo-caecal cases. Target lesion and leumen-within-leumen were the CT hallmarks on review. Retrospective barium enema review failed to show the intussusception. This may suggest the intussusception may have been recurrent or chronic. All 4 recovered uneventfully and remained well. One patient was referred for chemotherapy for intestinal lymphoma. Conclusion: Adult intussusception remains a rare cause of abdominal pain. The treatment almost always is surgical. Key words: Adult Intussusception